Exploring the influence of the five factor model of personality on the executive coaching process - Peacock, Kerry (My University, 2017)
Personality match between a dyadic pair in helping relationships has shown to improve the process and outcomes. Does the same apply to executive coaching? Coaching is deemed to be effective but why is this so? This study explored the role of personality similarities on the executive coaching process. By understanding the role personality plays it was anticipated that: understanding would be elicited as to why coachees select their particular coach; better matching could occur between the executive coach and coachee; the process would be more beneficial due to this similarity and there would be a better return on investment for organisations who could assess coaches and coachees and pair them accordingly based on similarities in personality. This study utilised the five factor model (FFM) of personality to explore the personalities of the coaches and coachees across eight coaching dyads. This study utilised qualitative methodology that of eight case studies made up of eight coaching dyads. All 16 respondents were interviewed using a semi-structured interview. This served as the primary data source. The interviews were recorded, transcribed and uploaded into Atlas ti software for analysis. Content analysis was used and a codebook was created inductively, resulting in 94 codes. The 16 respondents then completed the Wave personality questionnaire as the secondary data source. The assessments were uploaded onto Atlas ti software and were analysed qualitatively using content analysis. 34 codes were created deductively using psychometric principles and the Wave personality questionnaire’s measures. The 128 codes were then categorised into 27 categories and 11 themes. Similarity in personality did not appear to have as great an influence as was anticipated on the executive coaching process within each dyad. Although there was a perception of personality similarity in the majority of the cases, there was very little to substantiate this according to the FFM. This study argues that this perception of similarity is due to the rapport built between the coach and coachee as well as the adaptation of the coach to the coachee’s style and needs. This creates cognitive resonance and reinforcement-affect. Due to this perception it is evident that the training of coaches must focus on the coaching skills of openness and trust building. ii Despite similarities or dissimilarities in personality, all eight dyads indicated satisfaction with the coaching process, the coaching relationship and the outcomes. Across all coaches there was no similarity in personality factors. However, across all coachees, there were similarities in personality regarding change orientation, optimism and openness to feedback which speaks to coachee readiness. This study argues that coachee readiness should be assessed for in order to determine readiness for coaching which will allow for more beneficial outcomes. The relationship, rather than personality similarity, was deemed to be the fundamental component in the coaching process. A relationship based on trust and openness allows the coachee to become vulnerable. This vulnerability allows for validation of the coachee by the coach and it is this validation which allows for growth and development.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Business Executive Coaching Johannesburg, 2017
Keywords: Executive coaching--South Africa; Executives--Training of--South Africa; Personality tests